A new genus and species of the monticelliinae (eucestoda: Proteocephalidea), a parasite of pseudoplatystoma fasciatum (pisces: Siluriformes) from the paraná river basin (Argentina), with comments on microtriches of proteocephalideans - Arredondo, N.J. (2013)
This paper describes Regoella brevis gen. n. et. sp. n. (Proteocephalidea: Monticelliinae), a parasite of the intestine of the barred sorubim Pseudoplatystoma fasciatum (Linnaeus) from the Paraná River basin. The new genus is placed in the Monticelliinae because of the cortical position of the genital organs. It differs from all known genera included in the Monticelliinae by the following combination of characters: 1) a quadrangular scolex with a truncated conical apex and formed by four lobes separated by grooves; 2) uniloculate suckers of inverted triangular shape possessing a small cone-shaped projection at each corner of the anterior margin; 3) strobila consisting of a low number of proglottides; 4) testes arranged in one dorsal field; 5) a cirrus-sac, which represents more than one half of the proglottis width, cirrus surrounded by conspicuous chromophilic gland cells; 6) a butterfly-shaped and strongly lobulate ovary; and 7) formation of uterus of type 2. The examination of the tegument surface with scanning electron microscopy revealed the occurrence of three types of microtriches: acicular and capilliform filitriches and gladiate spinitriches. The new species is the eighth proteocephalidean reported from P. fasciatum, six of which are commonly found in the Amazon and Paraná River basins. © Institute of Parasitology, Biology Centre ASCR.